Clinical Value of Long Noncoding RNA HOTAIR as a Novel Biomarker in Digestive Cancers: A Meta-Analysis. (14th February 2018) - Zhang, Yun; Zhou, Yu; Xu, Tian; Tian, Wei; Yang, Chong; Wang, Xiaoxiao; Zhong, Shan; Ran, Qin; Yang, Hongji; Zhu, Shikai
HOX transcript antisense intergenic RNA has been reported to serve as an important prognostic biomarker in several types of cancers. However, the clinical value of HOX transcript antisense intergenic RNA in digestive cancers remains unclear. Therefore, we tried to investigate the clinical role of expression of HOX transcript antisense intergenic RNA as a prognostic indicator in digestive cancers by a meta-analysis. Literature collection was performed by searching the PubMed, Embase, Web of Science, and Cochrane Library databases (up to October 7, 2017). A quantitative meta-analysis was conducted to assess the eligible articles on the prognostic value of HOX transcript antisense intergenic RNA in digestive cancers. The pooled hazard ratios or odds ratios with 95% confidence intervals were used to evaluate the association between expression of HOX transcript antisense intergenic RNA and clinical outcomes. A total of 1844 patients from 22 studies were included in this meta-analysis. The results found a significant association between expression of HOX transcript antisense intergenic RNA and poor overall survival in digestive cancers (pooled hazard ratio = 2.19, 95% confidence interval, 1.86-2.57, P < .001). Furthermore, subgroup analysis showed that tumor type, region, Newcastle-Ottawa scale, and sample size did not alter the predictive value of HOX transcript antisense intergenic RNA as an independent factor for patients' survival. In addition, we also revealed that the clinicopathological characteristics such as differentiation, lymph node metastasis, tumor node metastasis (TNM) stage, and distant metastasis were positively related to expression of HOX transcript antisense intergenic RNA digestive cancers. In conclusion, our results suggested high expression of HOX transcript antisense intergenic RNA was correlated with poor clinical outcomes and may serve as a novel prognostic biomarker for patients with digestive cancers.